EFEKTIVITAS MEDIASI DALAM MENYELESAIKAN SENGKETA KONSUMEN DI BPSK KOTA PADANG - Daniel Jusari (Jurnal Public Administration, Business and Rural Development Planning, 2019)
Mediation as an alternative dispute resolution is considered to have beneficial forces, mediation can produce win-win solutions for the parties, and mediation is a relatively inexpensive and time-consuming segregation resolution process, dispute resolution through mediation efforts also has been known in the culture of traditional communities in Indonesia for a long time, especially in the Minangkabau community in West Sumatra known by the traditional philosophy of